Predictors of mortality in COVID-19 disease - Srikanth AK; Vijayalakshmi KP; Naveen S Kulkarni; Bhanuprathap Hoskeri; Hithashree C Shriyan; Nalla Yeshwanth Kirankumar (Asian Journal of Medical Sciences, 2022)
Background: COVID-19, an acute viral respiratory illness, was first noted in 2019, soon turned into pandemic with considerable mortality. With the objective of studying effect of comorbidities on COVID-19 disease severity and to identify laboratory markers associated with severe COVID-19 disease, we did a retrospective observational study in a tertiary care centre. Aims and Objectives: The objectives of this study were as follows: 1. To study effect of comorbidity on COVID-19 disease severity and 2. to identify laboratory markers associated with severe COVID-19 infection and mortality. Materials and Methods: This is an retrospective observational study conducted at SDMCMS&H, Dharwad from July 2020 to September 2020. A total of 402 cases who fall in the age group of 18 years and above were collected from medical record department. Statistical analysis used: The data were recorded in the Microsoft Excel sheet and analysis is done using Chi-square analysis and Cox linear regression method. Results: There were 402 patients whose data were collected. Out of 402 patients, 64 patients (15.92%) were in the age group of 18–39 years, 183 patients (45.52%) seen were in the age group of 40–60 years, 155 patients (38.56%) above 60 years, and consisting 291 male patients (72.39%) and 111 female patients (27.9%). Most common comorbidities seen were diabetes mellitus in 194 patients (48.26%) and hypertension in 182 patients (45.27%), followed by chronic kidney disease in 32 patients (7.96%) and ischemic heart disease in 24 patients (5.97%). Out 402 patients, 141 patients (35.07%) were on supplemental oxygen, which included 68 patients (48.23%) on low flow oxygen by face mask, seven patients (4.96%) were on non-rebreathing mask, 3 (2.13%) patients required NIV, and 63 patients (44.68%) required intubation and mechanical ventilation. It was found that uncontrolled diabetes rather than just presence of diabetes had significant impact on mortality with P=−0.0001 (95% CI OR 1.5–4.38). Patients with increased laboratory markers of inflammation such as Ferritin (95% CI OR 1.84–6.81) and LDH (95% CI OR 1.86–31.26) had strong association with mortality. The presence of thrombocytopenia showed significant association with mortality (95% CI OR 1.03–3.63). Conclusion: The presence of preceding uncontrolled hyperglycemia has significant effect on mortality. A state of hyperinflammation is directly associated with poor outcome.